Papaya seed extract lowers sperm concentrations, motility and viability in male mice - Wiryawan, Reryd Arindany; I'tishom, Reny; Purwaningsih, Sri (Folia Medica Indonesiana, 2016)
Indonesia is a developing country with a dense population, so the government carry on KB (Family Planning) program in which the targets are mostly women. Contraceptives are intended for women are birth control pills and IUD (Intra Uterine Device), whereas until now the contraceptive for men who are considered well-established are condom and vasectomy. Thus, the development of herbal medicine, which is cheap and affordable, makes it possible to be consumed in a long term with less meaningful side effects. Papaya seeds (Carica papaya) is one of the many plants used by communities to eradicate intestinal worms, menstrual laxative, and abortivum. Empirically papaya fruit, leaves, and seeds of papaya also contains carpaine, an alkaloid which is used as anthelmintic. Papaya seeds, which are edible and spicy in India are used for contraception. Alkaloid content in seeds of papaya can be antifertility herbal plants for males that can be measured from the quality of spermatozoa. Alkaloid compounds contained in papaya seeds can disrupt the hormone testosterone, which would interfere the sperm quality, making papaya seed potential to become a candidate for contraceptive.